2012
DOI: 10.15288/jsad.2012.73.783
|View full text |Cite
|
Sign up to set email alerts
|

Examining Risk and Protective Factors for Alcohol Use in Lesbian, Gay, Bisexual, and Transgender Youth: A Longitudinal Multilevel Analysis

Abstract: ABSTRACT. Objective: Lesbian, gay, bisexual, and transgender (LGBT) youth are at increased risk for alcohol misuse, but little is known about the psychosocial and demographic factors that are associated with these differences over time. The purpose of this study was to investigate change in alcohol use across development. We aimed to describe group/ demographic differences in alcohol use, the effects of psychosocial variables on drinking within persons (i.e., psychological distress, sexual orientation-based vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 61 publications
(64 reference statements)
9
91
0
5
Order By: Relevance
“…2 Lesbian, gay, bisexual, and transgender (LGBT) youth are at elevated risk of alcohol misuse, with drinking patterns that significantly increase linearly over time, more rapidly among male compared with female LGBT youth. 18 However, the overall pattern of results and correlates of alcohol use are strikingly similar to those of non-LGBT youth. 18 Rates of drinking were significantly lower in African American LGBT youth than in those of all other racial groups.…”
Section: Epidemiology Of Binge Drinkingmentioning
confidence: 81%
“…2 Lesbian, gay, bisexual, and transgender (LGBT) youth are at elevated risk of alcohol misuse, with drinking patterns that significantly increase linearly over time, more rapidly among male compared with female LGBT youth. 18 However, the overall pattern of results and correlates of alcohol use are strikingly similar to those of non-LGBT youth. 18 Rates of drinking were significantly lower in African American LGBT youth than in those of all other racial groups.…”
Section: Epidemiology Of Binge Drinkingmentioning
confidence: 81%
“…Furthermore, African American adolescents and adults have been found to drink and use drugs significantly less frequently compared to White individuals, 35,[41][42][43][44][45][46][47] and the association between substance use and sexual risk may not be consistent across racial groups.…”
Section: Substance Use and Unprotected Sexmentioning
confidence: 99%
“…GBT youth face multiple mental health disparities, including increased depressive symptoms, hopelessness, self-harm, and suicidality [1][2][3][4] as well as alcohol misuse 5,6 and substance use. 7,8 Several recent reports (e.g., Institute of Medicine 9,10 ) identify the extent of these disparities and advocate research on risk and protective factors for this population.…”
mentioning
confidence: 99%
“…Much of this work for LGBT youth has focused on family support, which has been negatively associated with hopelessness, depressive symptoms, suicidality, 13,15 and alcohol misuse. 5 Conversely, family rejection has been associated with increased suicide attempts, depression, and risk behaviors. 15 Research has also found family support to be more protective than peer or significant-other support for non-suicidal self-injury and alcohol use among adolescents 16 and for school performance among multiethnic sexual minority youth.…”
mentioning
confidence: 99%